2004
DOI: 10.1111/j.1460-8545.2004.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Networking and innovation: a systematic review of the evidence

Abstract: Recent work on competitiveness has emphasized the importance of business networking for innovativeness. Until recently, insights into the dynamics of this relationship have been fragmented. This paper presents a systematic review of research linking the networking behaviour of firms with their innovative capacity. We find that the principal benefits of networking as identified in the literature include: risk sharing; obtaining access to new markets and technologies; speeding products to market; pooling complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
1,026
0
61

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,301 publications
(1,168 citation statements)
references
References 134 publications
18
1,026
0
61
Order By: Relevance
“…It is widely accepted that acquiring external knowledge is crucial for the success of firms, particularly in the creative and high-technology industries (Pittaway et al, 2004). In the literature on regional learning and innovation it is often argued that firms located in innovative clusters benefit from other co-located organisations that create local knowledge spillovers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that acquiring external knowledge is crucial for the success of firms, particularly in the creative and high-technology industries (Pittaway et al, 2004). In the literature on regional learning and innovation it is often argued that firms located in innovative clusters benefit from other co-located organisations that create local knowledge spillovers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges encountered in this 233 study were similar to the limitations highlighted by Pittaway et al (2004) and Leseure 234 (2005). The key word search of "sustainability" is ambiguous, resulting in 235 publications from journals from multiple disciplines as well as topics outside the 236 scope of this study.…”
mentioning
confidence: 57%
“…In addition, there were risks associated with filtering 240 papers based on their abstracts. As highlighted by Pittaway et al (2004), much 241 depends on the quality of the written abstract, and consequently some relevant papers 242 may have been mislabelled and excluded for the final list. To mitigate part of this risk, 243 papers whose abstracts indicated that it may fall into category either "somewhat 244 relevant" or "very relevant" were read in detail to determine whether or not they 245 belong to the later.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The popular topic of relationship networks (Jarillo, 1988) has developed into several research focuses, such as alliances (Gulati, 1998), social networking (Granovetter, 1973;Burt, 1992;Coleman, 1988), learning (Khanna, Gulati, & Nohria, 1998), innovation (Pittaway, Robertson, Munir, Denyer, & Neely, 2004), and governance (Provan & Kenis, 2007). Further, these networks are the foundation of the more recent focus of coopetition (Bengtsson & Kock, 1999Bengtsson, Eriksson, & Wincent, 2010), which is an emerging topic of relationship strategies between firms and institutions.…”
Section: Introductionmentioning
confidence: 99%